Exploring Perceived Speaking Skills, Motives, and Communication Needs of Undergraduate Students Studying Japanese Language - Nam Hoang Tran; Katya Marinova; Van Hong Nghiem (MDPI AG, 2023)
This study investigated the perceived speaking skills of undergraduate students who were majoring or minoring in Japanese Studies at two universities in Vietnam and Bulgaria. It also examined the factors associated with students' speaking skills, their motives for studying Japanese, and their needs for communication with native Japanese speakers while proposing a hypothetical model linking these constructs. A total of 108 students participated in the cross-sectional online survey questionnaire, which included questions on personal information, perceived Japanese language skills, motives for studying Japanese, needs for communication with native Japanese speakers, and self-esteem. The data were analyzed using SPSS. The results showed that the respondents perceived their Japanese speaking skills level as lower than the other three skills. Factors such as age, year of enrollment, years studying Japanese, English level, co-living status, study abroad experience, and self-esteem were found to be associated with the perceived speaking skills of the respondents. Family-related factors, such as parents' education and the family's study abroad experience, were also found to be associated with perceived speaking skills. The study also validated three constructs of motives for studying Japanese, including being interested in Japan, being interested in communication, and being interested in going to Japan and highlighting the respondents' needs for communication with native speakers. The proposed model suggests that motives for studying Japanese influence perceived speaking skills and the need for communication with native Japanese speakers. The findings of this study have implications for Japanese language education, particularly in the development of teaching strategies that enhance students' speaking skills and provide opportunities for communication with native speakers. It also underscores the importance of understanding students' motives for studying Japanese, as these motivations can influence their language proficiency and the effectiveness of language education programs.